(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
This article explores the role of non-governmental organisations (NGOs) in the domestic implementation of the African Union Transitional Justice Policy (AUTJP). It uses Uganda as a prism through which to examine the implementation of two key constitutive elements of the AUTJP: criminal prosecutions and traditional justice. Besides reflections based on theauthor’s experience in Uganda, the analysis rests on an extensive study and review of literature and qualitative interviews. The article argues that NGOs have the potential to sequence the constitutive TJ elements of the AUTJP, where there are competing narratives of peace versus justice. While local NGOs are pivotal in fostering local ownership of TJ, the findings reveal thecritical role of NGO networks in the domestic implementation of TJ. The article concludes that there is a compelling case to be made for the continued involvement of NGOs in the domestic implementation of TJ